Efficacy of Sugammadex in Preventing Skin Test Reaction in a Patient With Confirmed Rocuronium Anaphylaxis: A Case Report. Issue 1 (1st July 2019) - Binczak, Marie; Fischler, Marc; Le Guen, Morgan
Abstract : The curative role of sugammadex has been challenged in several observations of rocuronium-induced anaphylaxis because sugammadex may not completely encapsulate the molecule of rocuronium. In such conditions, rocuronium remains able to cause immunoglobulin E cross-linkage and the anaphylaxis mechanism can continue. We describe a case of rocuronium-induced anaphylaxis in which clinical improvement followed sugammadex administration. Intradermic skin tests confirmed rocuronium immunoglobulin E–mediated anaphylaxis but also showed intradermal injection of mixing in equal molecular ratio of sugammadex with rocuronium preventing rocuronium anaphylactic skin reaction. This observation demonstrates the efficacy of sugammadex to prevent rocuronium interaction with the skin immune system.